Early education in a global context - Sutterby, John A., 1966- (Bingley, U.K. : Emerald, 2012)
This volume of Advances in Early Education and Day Care examines early education from perspectives around the globe. The eight chapters come from a variety of locations including China, Israel, Sweden, Italy, Greece, Zambia, The United States and Canada. These chapters discuss professional development in several contexts, childrens understandings and programs for children. This volume should give the reader an idea of the range of work that is being done around the globe. The unique feature of this volume is that it brings together insider perspectives on early education in different contexts. Each author/s has discussed what is going on in their own context. The Reggio Emilia educational program from Northern Italy has over the last 3 decades had a global impact on early education. This volume seeks to add to the knowledge brought from other diverse sources. The target audience for this book are educational researchers and program developers who are seeking information about international programs.
Introduction / John A. Sutterby -- ch. 1. Kindergarten curriculum reform in mainland China and reflections / Yue-Juan Pan, Xia Li -- ch. 2. Bridging cultural differences using digital tools for the professional development of early childhood teachers in two global contexts / Darlene DeMarie, Susan Weber, Victoria Damjanovic -- ch. 3. Florida PERKS : a statewide professional development initiative for prekindergarten teachers / Rebecca A. Marcon, Phyllis K. Kalifeh, Beverly G. Esposito, Lynn C. Hartle, Saralyn R. Grass -- ch. 4. Using learning study as in-service training for preschool teachers / Mona Holmqvist Olander, Agneta Ljung-Djärf -- ch. 5. Improving children's attitudes and awareness toward a healthy lifestyle in early childhood : a five-European country intervention program / Vasilis Grammatikopoulos, Athanasios Gregoriadis, Evridiki Zachopoulou -- ch. 6. Development and sustainability of high-quality early childhood education programs in Zambia / Iheoma U. Iruka, Mary Faith Mount-Cors, Samuel L. Odom, Sandra Naoom, Melissa Van Dyke -- ch. 7. Philosophy for children and the developmental process of dialogical critical thinking in groups of preschool children / Marie-France Daniel, Mathieu Gagnon, Jean-Charles Pettier -- ch. 8. The effectiveness of community of practice in supporting Israeli kindergarten teachers dealing with an emotionally laden topic / David Brody, Avigail Friedman.
Includes index.
Print version record
Keywords: Education -- Preschool & Kindergarten; Education -- Elementary; Education -- Multicultural Education; Pre-school & kindergarten; Schools; Early childhood education